Preparation of Pedagogical Workers to Socialization of Youth (20th of XX Century) - Tafintseva, Svitlana (Pedagogical Discourse, 2015)
In the article an author carries out the analysis of specific of professional preparation of future teachers to socialization of rising generation in 20th of XX century. The features of maintenance of training of pedagogical personnel are certain in accordance with the requirements of soviet society. On the basis of the proper source base an author is carry out the attempt of historical pedagogical analysis of professional preparation of future teachers to socialization of students, which was carried out at active position of power, to the party-state machinery on clear ideological basis of getting up of ideological and political level and scientifically methodical qualification of teachers of primary, septennial and secondary schools of USSR, what came forward a social base for propaganda and active introduction of measures, which promote the development and forming of soviet personality of schoolboy. The main tendencies in professional preparation to socialization of growing generation through its political education for the rising cultural political level of youth, as an earnest of building of socialistic society, are established. The maintenance and forms of preparation of future teachers are generalized; it is indicated on importance of historical experience of the past for a modern theory and practice of professional preparation of teachers to socialization of rising generation. During 20th of ХХ century an accent came true in preparation of pedagogical workers to socialization of schoolchildren on a systematic increasing of their ideal-theoretical level and professional qualification, working on marxism-leninism theory, party and governmental decisions, questions of theory of labour and polytechnic studies and communist education of rising generation, that assisted upgrading, breeding of education, socialization of youth.